Improving knowledge, attitudes, and practices on dengue and diarrhea in rural primary school students, their parents, and teachers in Colombia: A cluster-randomized controlled trial. - Diana Sarmiento-Senior; Maria Ines Matiz; Sandra Vargas-Cruz; Juan Felipe Jaramillo; Victor Alberto Olano; Audrey Lenhart; Thor Axel Stenström; Neal Alexander; Hans J Overgaard (PLoS Neglected Tropical Diseases, 2022)
Background Improved education on water-related diseases in schools could help to reduce disease burden. This paper presents specific results on knowledge, attitudes and practices (KAP) of a cluster-randomized controlled trial to reduce diarrheal disease and dengue entomological risk factors in rural primary schools in Colombia. The aim was to investigate whether enhanced educational interventions on dengue and diarrheal disease in schools could improve KAP scores related to these diseases in students and teachers in rural primary schools, as well as the students' parents. Methodology/principal findings A factorial cluster-randomized controlled trial was carried out in 35 rural primary schools in two municipalities in Cundinamarca, central Colombia. Schools were randomized into four arms: interventions related to diarrheal disease (DIA), dengue (DEN), both (DIADEN), or no interventions (control, CON). Both educational and physical interventions to reduce risk factors of dengue and diarrhea were implemented. Comprehensive teachers' manuals were developed and deployed to guide the learning activities. The intervention was carried out over two school years. The knowledge scores of students receiving dengue interventions (DEN, DIADEN) increased by 1.16 point score (0.75-1.56, p<0.001) and those receiving diarrhea interventions (DIA, DIADEN) increased by 1.15 point score (0.67-1.63, p<0.001). The attitude and practice scores of students receiving the diarrhea interventions increased (Attitudes: 0.41 [0.11-0.71, p = 0.01]; Practices: 0.33 [0.01-0.65, p = 0.042]), but not for those receiving the dengue interventions (p = 0.31 and p = 0.08, respectively). Conclusions/significance There were increases in knowledge scores among students, their teachers and their parents for both diseases. However, the attitudes and practices components were not affected to the same extent. The hypothesis that the students would disseminate knowledge acquired from the educational interventions to their parents was confirmed for dengue, but not for diarrhea. Trial registration ISRCTN40195031 The trial is registered in the Current Controlled Trials under Infections and Infestations category.